PERBANDINGAN KESETARAAN NILAI DOSIS SERAP BOLUS LILIN DAN CONFORMAL BOLUS TERHADAP JARINGAN LUNAK PADA PERENCANAAN TEKNIK RADIOTERAPI - Yudha Aries Pratama; Muhammad Fadli (JRI (Jurnal Radiografer Indonesia), 2018)
Backgroud: The purpose of this paper is to measure equality volue of wax bolus and conformal bolus againts soft tissue. This research is qualitative descriptive. This study is observed at Radiotherapy Department MRCCC Siloam Hospitals Semanggi. The methode of this research is measure, comparing a result and the research instrument used is electrometer and paper work to notice a result of measuement. Methods: The device used is linear accelerator with type Clinac iX, ionization chamber adn electrometer. please note the room temperature and room preasure before measuring. Stack 10 plate of slab phantom with 1cm thickness and 30x30cm2 wide on the linac table. After that put ionization chamber into the 10th slab phantom, add more 9 plate of slab phantom with same thickness and 1 plate of slab phantom with 0.5cm thickness. Arrange the stack of slab phantom until the position in the middle of lasser in that room. Connect the ionization chamber with electrometer who locate in oprator room. In order to we can see the result at oprator room. Stacks a slab phantom , paraffin wax bolus and conformal bolus each having a thickness 0.5cm alternately. Measuring 5 times in every material with 6MV and 15MV energy. Result: The result is in 10-8C. That result must be converted into absorb dose (cGy). Compare the result of wax bolus and conformal bolus against the result of slab phantom.